2020
DOI: 10.18632/aging.102752
|View full text |Cite
|
Sign up to set email alerts
|

A high neutrophil-to-lymphocyte ratio predicts hemorrhagic transformation of large atherosclerotic infarction in patients with acute ischemic stroke

Abstract: Increasing evidence suggests that inflammation is associated with the development of acute ischemic stroke (AIS). The neutrophil-to-lymphocyte ratio (N/L) is an important marker of inflammation and is highly correlated with mortality in stroke patients in recent studies. The N/L of patients who experience hemorrhagic transformation (HT) after AIS is know, but any relationship between N/L and large artery atherosclerosis (LAA) remains unclear, this is our present topic. We enrolled 185 patients with LAA-type HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Previous studies exhibited that NLR, PLR, and LMR could predict the clinical outcome in AIS patients [ 16 , 18 , 40 ]. NLR and LMR can also foretell HT after ischemic stroke [ 41 , 42 ]. Moreover, high NLR and PLR might be associated with symptomatic internal carotid artery stenosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exhibited that NLR, PLR, and LMR could predict the clinical outcome in AIS patients [ 16 , 18 , 40 ]. NLR and LMR can also foretell HT after ischemic stroke [ 41 , 42 ]. Moreover, high NLR and PLR might be associated with symptomatic internal carotid artery stenosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Association of NLR and LMR with hemorrhagic transformation was also noted in patients who did not receive IV tPA. [19][20][21] Now, we have been extended this observation to other indices. In addition, although we used very stringent criteria, we were able to detect clinically useful, albeit moderate, thresholds for both NLR (6.65) and SII (1781) for PH2 type hemorrhage occurrence after IV tPA (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…The external validation was then a cohort of patients from the same center at different time periods. In our previous study, neutrophil-to-lymphocyte ratio was found to be one of the risk factors for HT in patients with LAA, and the model developed accordingly had an AUC of 0.832, which also predicted the outcome well for both PH and HI (8). In another study of ours, it was found that cardiogenic parameters were risk factors for worse prognosis of patients with non-LAA AIS, the nomogram based on cardiogenic parameters and NIHSS scores established was a good predictor of the prognosis of patients with non-LAA,and its AUC reached 0.954 (9).…”
Section: Discussionmentioning
confidence: 91%